EFFECT OF THINNING ON GROWTH AND WOOD PRODUCTION OF NATURALLY REGENERATED 8-YEAR-OLD ACACIA MANGIUM WILLD. PLANTATION ON ABANDONED MINING AREA, SOUTHERN THAILAND - Jetsada Wongprom; Somporn Maelim; Wasan Chandaeng; Sakhan Teejuntuk; Monthathip Sommeechai; Decha Duangnamon (BIOTROPIA, 2023)
Thinning is an important practice for promoting growth and maintaining forest plantation for wood production from the remaining trees. In this study, thinning was carried out in a naturally regenerated 8-year-old Acacia mangium plot in the Phangnga Forestry Research Station. Three thinning schemes, with 175 (T1), 300 (T2) and 600 (T3) remaining trees/ha, were compared with the control (no thinning) of 831 trees/ha. The diameter at breast height (DBH) and height (H) of the trees were measured. The differences in growth, current annual increment (CAI), aboveground biomass, and stem volume (V) were analyzed. We observed that the thinning of A. mangium increased the growth rate, with the DBH being clearly affected by thinning. CAIDBH increased significantly, with the DBH class of thinned A. mangium plots also improving after thinning. The stem volume and aboveground biomass of T3 plot was similar to the control plot after thinning. In addition, the number of large saw logs was the highest in T3 plot. The large saw logs can be used for multi-utilization and have a high value. These results suggest that thinning can promote stem growth, and increase the proportion of large saw logs in naturally regenerated A. mangium stands.